THE ROLE AND SCIENTIFIC ROLE OF TRANSLATION AND TRANSLATION STUDIES IN SOCIETY - Kiyаsоvа Rа’nо (Журнал иностранных языков и лингвистики, 2023)
Our article discusses the role of translation and translation studies in society. The translation is considered one of the most important means of inter-ethnic understanding and understanding and holds a key position in the formation of national languages and literature and their development.